2012
DOI: 10.4102/sajems.v15i2.212
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the suite of measures of gender-based discrimination: gender differences in ablution facilities in South Africa

Abstract: International treaties, national legislation and local by-laws all advocate the equal treatment of men and women, but claims of gender-based discrimination continue. Indicators of discrimination against women, including employment ratios and differences in income, show that there have been considerable gains in the recent past. These measures are, however, often biased. In this study a different, specific and concrete method of describing and detecting discrimination is presented, namely the difference in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…This gave birth to the formation of a government department, the Department of Women, Children and Persons with Disability which was set up to deal with issues that affect women, girls and the vulnerable. Despite these efforts, gender inequality is believed to still be prevalent in various sectors and situations in South Africa such as the economy (Hlekiso & Mahlo 2006), corporate sector (Moletsane & Reddy 2008), service delivery (Steyn 2012), training and development (Chinyamurindi & Louw 2010), and within the classroom (Hammond et al 2007;Mahlomaholo 2011). This research answers calls for studies that focus on the role of science and technology on the lives of people (Reddy et al 2013) particularly within education research (Flipsen & van der Weide 2009).…”
Section: Putting This Research Into Contextmentioning
confidence: 99%
“…This gave birth to the formation of a government department, the Department of Women, Children and Persons with Disability which was set up to deal with issues that affect women, girls and the vulnerable. Despite these efforts, gender inequality is believed to still be prevalent in various sectors and situations in South Africa such as the economy (Hlekiso & Mahlo 2006), corporate sector (Moletsane & Reddy 2008), service delivery (Steyn 2012), training and development (Chinyamurindi & Louw 2010), and within the classroom (Hammond et al 2007;Mahlomaholo 2011). This research answers calls for studies that focus on the role of science and technology on the lives of people (Reddy et al 2013) particularly within education research (Flipsen & van der Weide 2009).…”
Section: Putting This Research Into Contextmentioning
confidence: 99%
“…According to Buhai, Portela, Teulings and Van Vuuren (2014), income increases with seniority, whilst Ebrahim (2017) described seniority as a justification for an income difference, regarded as fair. The entry of highly educated women into male occupations and the effect thereof on the narrowing of the gender pay gap is well documented in the literature (Drolet & Mumford, 2012;Steyn, 2012;Steyn & Jackson, 2015).…”
Section: What Is the Status Of Occupational Gender Segregation?mentioning
confidence: 98%
“…The study found that significantly more men than women are used in the formal sector. The implication is that women are still vastly under-represented in employment, and discrimination being a factor cannot be ruled out (Gnesi, De Santis, & Cardinaleschi, 2016;Steyn, 2012), as the fact remains that women constitute more than 50% of working-age adults in South Africa (Motsoeneng & Kahn, 2014;Steyn, 2012).…”
Section: What Is the Status Of Occupational Gender Segregation?mentioning
confidence: 99%
See 1 more Smart Citation